Adaptation, Reliability, and Validity of the Auditory Skills Checklist (ASC) for Bengali Speaking Children with Severe to Profound Sensorineural Hearing Loss with Hearing Aids - Rahman, Istiak; Hasan, Mahedi (Makara Journal of Health Research, 2025)
Background: The audiologic assessment guidelines of the American Speech-Language-Hearing Association (ASHA) encouraged functional auditory skills assessment, appropriate for age. The Auditory Skills Checklist (ASC) assessment tool was developed from the necessity to assess the auditory skills of young children with Sensorineural Hearing Loss (SNHL). The aim of this study was to adapt a Bengali version of the ASC checklist from the original English version and then to test its reliability and validity. Methods: The method of forward-backward translation and cognitive debriefing was employed to produce a culturally sensitive Bengali version of the checklist. The data was analyzed for the internal consistency of items, inter-rater agreement of items, temporal reliability, and convergent validity. Results: The adapted Bengali version of the ASC produced excellent internal consistency (Checklist total = Cronbach’s alpha 0.980 and domain specific Cronbach’s alpha of 0.958, 0.921, 0.908 and 0.932 respectively), substantial level of inter-rater agreement (κ = 0.668 to 0.845 and p < 0.01), excellent temporal reliability (ICC 0.974 and p < 0.01) and convergent validity (AVE > 0.5). Conclusion: The adapted version of the ASC showed excellent reliability and validity to facilitate functional auditory skills assessment and intervention.